SISTEM INFORMASI PEMBAYARAN KREDIT KENDARAAN SEPEDA MOTOR PADA CV. PUTRA PERSADA - Rudianto Rudianto; Edy Rakhmat (Jurnal Ilmiah Sains dan Teknologi, 2019)
with the progress of information technologi develompent. It has increasingly triggered economic activities in all fields.Among these economic activities are bussinesses in the field of automotive product sales. So that at this time many emerging companies engaged in the field of automotive Loan financing.One such campany is CV. Putra Persada having ITS address at Rangkas Bitung as the official distributor of Yamaha motorcycles sales. Payment of automotive loans id the main activity of CV. Putra Persada besides payment in cash. Because as an economically credit purchase bring more profits than cash purchase. This credit purchase can also have a negative impact on the company. The negative impact can be caused by mismanagement of the company. In managing credit related data such as consumer data and navigation data. It type related to credit such as consumer data and credit payment data. Addressing the problems container in the CV. Putra Persada we Made a solution by analyzing and designing a more efficient and effective information system' which ia also our final project, which we titles "Motorcycle credit payment information system' at CV. Putra Persada"